Coreografia das sensações : corpo, dança e filosofia - Ana Rita Nicoliello Lara Leite (2022)
The desire that animates this dissertation is to contribute to a philosophy of the living body, by the composition of philosophical concepts, collected mainly from Gilles Deleuze’s philosophy, and some thoughts and practices from contemporary dance. The thesis is composed of five movements:1) In DRAWING, inspired by the greek myth of the labyrinth, I expose some paradoxes concerning the body; I trace the strategy of dealing with dance, its force and meaning operations, based on the concept of gesture and its founding element, gravity; finally, I delimit my field, proposing the concept of untimely dance understood from three perspectives: the (aesth)etic of difference, practical epistemology and choreopolitics; 2) In FALLING, I explore the theme of thought by a dialogue between contact improvisation dancers and Deleuze. I propose a modulation of the concepts of thought and consciousness not based on mind-body dualism, but grounded on Deleuzian concepts of actual and virtual, as well as on the concept sensation of consciousness, inspired in Steve Paxton and Nita Little. 3) In PEOPLING, I engage myself in thinking about the space, the sensible and its constituent elements: the intensities. I start from Xavier Le Roy’s performance Self Unfinished, to defend that dance is a program to constitute and to put into circulation bodies without organs or bodies of sensation. 4) In REPEATING, I start with some repetition practices in dance universe to think about time. I propose an analysis of the three syntheses of time as well as the Deleuze and Guattari’s concept of refrain to explore the repetition in dance, as the return of the difference.